Surgical safety checklists: a review. Issue 3 (18th April 2013) - Tang, Reuben; Ranmuthugala, Geetha; Cunningham, Frances
Abstract Background Surgical checklists are designed to improve patient outcomes following surgery. While such checklists have been widely implemented worldwide, few studies examine surgical checklists within an Australian context. For this purpose, we have performed a literature review using data from OECD member nations to determine the effectiveness of surgical checklists in improving patient outcomes and factors that contribute to their successful implementation. Method The databases, Pubmed, Medline, EMBASE, Cochrane and CINAHL were searched using the keywords ('surgical' AND 'checklist') and ( (surgical) AND checklist) AND ( (implementation) OR (utilization) OR (usage) ). Studies were limited to those written in the English language, peer‐reviewed, published between January 2000 and December 2012, and including an abstract. Results Our search yielded 2242 papers, of which 72 papers were identified for their potential relevance and selected for full text review. Of these, nine papers met the inclusion criteria and were reviewed in detail. Evidence that supports the use of surgical checklists in countries with a large number of protocols already in place is limited. Adequate checklist implementation plays a central role in checklist effectiveness, which in turn is dependent on multiple factors. Conclusion Although evidence from OECD member countries is non‐conclusive, it does suggest that surgical checklists, when effectively implemented, have the potential to be effective at reducing complication and mortality rates following surgery. Within an Australian context, more studies are needed to fully establish the potential effectiveness of surgical checklists and to monitor checklist use compliance in order to ensure greater patient safety.